Neoconservatism : why we need it - Murray, Douglas, 1979- (Encounter Books, 2006)
Neoconservatism: Why We Need It is a defense of the most controversial political philosophy of our era. Douglas Murray takes a fresh look at the movement that replaced Great-Society liberalism, helped Ronald Reagan bring down the Wall, and provided the intellectual rationale for the Bush administration's War on Terror. While others are blaming it for foreign policy failures and, more extremely, attacking it as a "Jewish cabal," Murray argues that the West needs Neoconservatism more than ever. In addition to explaining what Neoconservatism is and where it came from, he argues that this American.